Preparation method, product and application of catalyst

By introducing Ce additives and NaBH4 reduction treatment in copper-zinc-aluminum catalysts, electron transfer paths are constructed, and the problem of unstable catalyst sintering and selective conversion rate at high temperatures is solved, and the efficient catalytic performance of CO2 hydrogenation is achieved and stability.

CN119114086AActive Publication Date: 2024-12-13TAIYUAN UNIVERSITY OF TECHNOLOGY

Patent Information

Application Number
CN202411221399.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-02
Publication Date
2024-12-13
Estimated Expiration
2044-09-02

AI Technical Summary

Technical Problem

The existing CO2 hydrogenation catalysts for methanol production are limited by the high temperature sintering, selectivity and unstable conversion of copper components, which limit their industrial applications.

Method used

Ce additives were introduced into the copper-zinc-aluminum catalyst, and Ce4+/Ce3+ and Cu2+/Cuδ+/Cu0 redox electron pairs were constructed through NaBH4 reduction treatment, electron transfer paths were built, the acid and alkalinity of the catalyst and the oxygen vacancies were adjusted, and the catalytic performance was improved. .

Benefits of technology

The catalytic performance and stability of CO2 hydrogenation to produce methanol is significantly improved, the CO2 conversion rate and methanol selectivity of the catalyst are improved, and the sintering and aggregation of copper components is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119114086A_ABST
    Figure CN119114086A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of catalysts and methanol preparation through CO2 hydrogenation, in particular to a preparation method of a catalyst, a product and application. The preparation method of the catalyst comprises the following steps: adding a copper-zinc-aluminum catalyst into a cerous nitrate aqueous solution, uniformly mixing, and stirring in a water bath to obtain a mixed solution; adding an alkali solution of NaBH4 into the mixed solution, and reacting to obtain a precipitate; and carrying out ultrasonic treatment on the precipitate, washing, drying, grinding and roasting to obtain the catalyst. The assistant Ce is introduced into the copper-zinc-aluminum catalyst, sodium borohydride (NaBH4) is used for reduction, Ce < 4 + > / Ce < 3 + > and Cu < 2 + > / Cu < delta + > / Cu < 0 > redox electron pairs are constructed, an electron transfer pathway is established, and the catalytic performance of methanol preparation through CO2 hydrogenation is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalyst and CO2 hydrogenation to methanol, and in particular to a preparation method, product and application of a catalyst. Background Art

[0002] In the past few decades, the fossil energy that humans have continuously consumed to meet the needs of economic and social development has eventually turned into CO2 and "fed back" to humans, causing environmental problems such as rising temperatures, rising sea levels, and extreme weather. Energy conservation and emission reduction, and sustainable development have become difficult problems facing the world. Faced with this problem, my country has actively responded and put forward the goal of "carbon peak and carbon neutrality" to alleviate the global energy, environmental, and climate crises.

[0003] Using CO2 as a C1 resource and combining it with "green hydrogen" to convert it into a high-value-added chemical - methanol is an effective way to solve this crisis. It can not only achieve a green carbon cycle, but also effectively alleviate human dependence on fossil energy. The technical core of CO2 hydrogenation to methanol is the development of efficient and stable catalysts. The catalysts currently used for CO2 hydrogenation to methanol are mainly: non-precious metal catalysts (mainly Cu-based catalysts) and precious metal catalysts. Non-precious metal catalysts have potential advantages in industrial applications due to their low prices, but the "seesaw" effect of methanol selectivity and CO2 conversion rate and the sintering problem caused by lattice migration of Cu components at high temperatures have always been bottlenecks that plague its industrialization. Summary of the invention

[0004] Based on the above content, the present invention provides a preparation method, product and application of a catalyst.

[0005] To achieve the above object, the present invention provides the following solutions:

[0006] One of the technical solutions of the present invention is a method for preparing a catalyst, comprising the following steps:

[0007] The copper-zinc-aluminum catalyst is added into the cerium nitrate aqueous solution and mixed evenly, and then stirred in a water bath to obtain a mixed solution;

[0008] Adding an alkaline solution of NaBH4 into the mixed solution to react and obtain a precipitate;

[0009] The precipitate is subjected to ultrasonic treatment, washed, dried, ground and calcined to obtain the catalyst.

[0010] The second technical solution of the present invention is a catalyst prepared according to the above-mentioned preparation method.

[0011] The third technical solution of the present invention is the application of the above catalyst in the production of methanol by CO2 hydrogenation.

[0012] The fourth technical solution of the present invention is a two-stage catalyst for CO2 hydrogenation to methanol, which is prepared from the catalyst and the commercially available industrial methanol Cu / ZnO / Al2O3 catalyst. (When the two-stage catalyst is used for CO2 hydrogenation to methanol, the catalyst (CZA-Ce-0.1NaBH4) is located near the air inlet end, and the commercially available industrial methanol Cu / ZnO / Al2O3 catalyst is near the air outlet end).

[0013] The present invention discloses the following technical effects:

[0014] The invention introduces Ce as an auxiliary agent into the copper-zinc-aluminum catalyst and uses sodium borohydride (NaBH4) for reduction to construct Ce. 4+ / Ce 3+ and Cu 2+ / Cu δ+ / Cu 0 The redox electron pairs build an electron transfer pathway and improve the catalytic performance of CO2 hydrogenation to methanol. In addition, the introduction of Ce can also adjust the acidity and alkalinity of the catalyst and bring abundant oxygen vacancies to the catalyst, which is conducive to the efficient activation and hydrogenation conversion of CO2. The invention uses NaBH4 reduction treatment to introduce more Ce into the catalyst. 4+ / Ce 3+ The redox electron pairs improve the electron transfer efficiency within the catalyst and further enhance the catalytic performance of CO2 hydrogenation to methanol. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0016] Figure 1 The catalytic performance (a), CO2 conversion rate at 3MPa (b), methanol selectivity at 3MPa (c), CO2 conversion rate at 4MPa (d) and methanol selectivity at 4MPa (e) of the catalysts prepared in Example 1 of the present invention and Comparative Example 1.

[0017] Figure 2 The catalytic performance (a), methanol selectivity (c), CO2 conversion rate (d) of the catalysts in Example 2 and Comparative Example 2 at 3MPa and the methanol selectivity and CO2 conversion rate (b) of the CZA-Ce-0.1NaBH4 / industrial methanol catalyst 504h reaction. DETAILED DESCRIPTION

[0018] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0019] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0020] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0021] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0022] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0023] The "normal temperature" or "room temperature" mentioned in the present invention, unless otherwise specified, means 20-30°C.

[0024] The first aspect of the present invention provides a method for preparing a catalyst, comprising the following steps:

[0025] The copper-zinc-aluminum catalyst is added into the cerium nitrate aqueous solution and mixed evenly, and then stirred in a water bath to obtain a mixed solution;

[0026] Adding an alkaline solution of NaBH4 into the mixed solution to react and obtain a precipitate;

[0027] The precipitate is subjected to ultrasonic treatment, washed, dried, ground and calcined to obtain the catalyst.

[0028] The purpose of ultrasonic treatment of the precipitate is to make the reduction more complete.

[0029] In some embodiments of the present invention, the concentration of the cerium nitrate aqueous solution is 0.01-0.1 mol / L; the concentration of the copper-zinc-aluminum catalyst in the mixed solution is 60-150 mg / mL; the temperature of the water bath stirring is 303-363 K, and the time is 0.5-4 h. The mixing method is ultrasonic treatment for 0.5-2 h.

[0030] In some embodiments of the present invention, the concentration of NaBH4 in the alkaline solution of NaBH4 is 0-0.20 mol / L; the alkaline solution of NaBH4 also includes NaOH or KOH; the molar ratio of the NaBH4 to the NaOH or KOH is (1-3):1.

[0031] In some embodiments of the present invention, the volume ratio of the NaBH4 alkaline solution to the mixed solution is (1-3):1; the reaction is specifically carried out at room temperature for 1-5 hours. The NaBH4 alkaline solution is added dropwise.

[0032] In some embodiments of the present invention, the ultrasonic treatment time is 0.5 to 2 hours; the drying temperature is 323 to 353 K, and the time is 8 to 15 hours; the washing is specifically washing with deionized water; the calcination temperature is 583 to 633 K, and the time is 3 to 6 hours.

[0033] In some embodiments of the present invention, the method for preparing the copper-zinc-aluminum catalyst comprises the following steps:

[0034] Dissolve copper salt, zinc salt and aluminum salt in water according to the molar ratio of Cu:Zn:Al=2:1:1.2 to obtain solution A;

[0035] Dissolve the hydroxide and carbonate in water to obtain solution B;

[0036] The solution A and the solution B are simultaneously dropped into water, stirred, and aged, and the obtained solid is dried and calcined to obtain the copper-zinc-aluminum catalyst;

[0037] The hydroxide is NaOH or KOH; the carbonate is Na2CO3 or K2CO3.

[0038] In some embodiments of the present invention, the copper salt is at least one of copper nitrate, copper sulfate, copper acetate or copper chloride; the zinc salt is at least one of zinc nitrate, zinc chloride, zinc sulfate or zinc acetate; the aluminum salt is at least one of aluminum nitrate, aluminum sulfate, aluminum chloride or aluminum acetate; the concentration of zinc salt in solution A is 0.2-1.2 mol / L; the concentration of hydroxide in solution B is 1-2 mol / L; the molar ratio of the hydroxide to the carbonate is 2:1; the volume ratio of solution A to solution B is 1:(1-4); the aging temperature is 353K and the time is 10-15h; the drying temperature is 343-363K and the time is 10-15h; the calcination temperature is 583-633K and the time is 3-6h.

[0039] The second aspect of the present invention provides a catalyst prepared according to the above preparation method.

[0040] The third aspect of the present invention provides an application of the above catalyst in CO2 hydrogenation to methanol.

[0041] The present invention is based on CuZnAl non-precious metal catalyst, and improves the dispersion of Cu species and prevents its sintering and aggregation through a hydrotalcite-like structure with rich pores, large specific surface, skeleton metal ions and adjustable acidity and alkalinity, and introduces an auxiliary agent Ce into the catalyst and uses sodium borohydride (NaBH4) to reduce it to construct Ce. 4+ / Ce 3+ and Cu 2+ / Cu δ+ / Cu 0 The redox electron pairs build an electron transfer pathway and improve the catalytic performance of CO2 hydrogenation to methanol. In addition, the introduction of Ce can also adjust the acidity and alkalinity of the catalyst and bring abundant oxygen vacancies to the catalyst, which is conducive to the efficient activation and hydrogenation conversion of CO2. Therefore, the invention uses the NaBH4 reduction treatment method to try to introduce more Ce into the catalyst. 4+ / Ce 3+ Redox electron pairs improve the electron transfer efficiency within the catalyst to further improve the catalytic performance of CO2 hydrogenation to methanol.

[0042] The fourth aspect of the present invention provides a two-stage catalyst for CO2 hydrogenation to methanol, which is prepared from the above catalyst and a commercially available industrial methanol Cu / ZnO / Al2O3 catalyst. When the two-stage catalyst is used for CO2 hydrogenation to methanol, the catalyst (CZA-Ce-0.1NaBH4) is located near the air inlet end, and the commercially available industrial methanol Cu / ZnO / Al2O3 catalyst is located near the air outlet end.

[0043] The fifth aspect of the present invention provides the use of the above-mentioned two-stage catalyst for CO2 hydrogenation to methanol in CO2 hydrogenation to methanol, comprising the following steps:

[0044] The catalyst (CZA-Ce-0.1NaBH4) and the industrial methanol Cu / ZnO / Al2O3 catalyst were placed in series in a fixed bed reactor in a volume ratio of 1:1, wherein the CZA-Ce-0.1NaBH4 catalyst was located near the air inlet end, and the commercially available industrial methanol Cu / ZnO / Al2O3 catalyst was located near the air outlet end; the reaction was carried out at 3MPa, 6000h -1 and CO2:H2=1:3.

[0045] Unless otherwise specified, the raw materials used in the embodiments of the present invention can be obtained through commercial sources.

[0046] The present invention is further described below by way of examples.

[0047] Example 1

[0048] Step 1, Preparation of Copper Zinc Aluminum CZA Catalyst

[0049] The copper-zinc-aluminum CZA catalyst was prepared by a co-precipitation method, and the steps were as follows: 14.50 g Cu(NO3)2·3H2O, 8.92 g Zn(NO3)3·6H2O, 13.51 g Al(NO3)3·9H2O (maintaining the following molar ratio n Cu :n Zn :n Al =2:1:1.2) was dissolved in 100 mL of deionized water to obtain solution A. 8 g of NaOH (1 mol / L) and 10.79 g of Na2CO3 (0.5 mol / L) were dissolved in 200 mL of deionized water, which was recorded as solution B. At 298 K and keeping the pH of the mixed solution at 9-10 during the titration, solutions A and B were added dropwise to 100 mL of deionized water at the same time. After stirring for 1 hour, the obtained mixture was aged at 353 K for 12 h and then cooled to room temperature. After filtering and washing to pH = 7, the obtained solid was dried in air at 353 K for 12 h, and then calcined at 623 K in air atmosphere for 4 h to obtain CZA catalyst.

[0050] Step 2, impregnation of Ce and treatment with NaBH4

[0051] 2.17 g of Ce(NO3)3·6H2O (0.05 mol / L) was dissolved in 100 mL of deionized water, and 13.5 g of the above CZA catalyst was dissolved in the solution and ultrasonically treated for 30 min.

[0052] The mixture was transferred to a 353K water bath and stirred for 1 h. A freshly prepared mixed solution of NaBH4 (x mol / L) and NaOH (purity 98%) (molar ratio n NaBH4 :n NaOH =2:1) ​​100mL was added dropwise to the solution after the water bath, and the reaction was continued for 3h. The obtained precipitate was ultrasonically treated for 30min, washed with deionized water and placed in a vacuum drying oven at 333K overnight. After grinding, it was calcined at 623K for 4h under a nitrogen atmosphere to obtain a CZA-Ce-xNaBH4 catalyst (wherein x is the concentration of the NaBH4 solution; when x=0, the corresponding catalyst is marked as CZA-Ce; when x=0.02, the corresponding catalyst is marked as CZA-Ce-0.02NaBH4; when x=0.1, the corresponding catalyst is marked as CZA-Ce-0.1NaBH4; when x=0.18, the corresponding catalyst is marked as CZA-Ce-0.18NaBH4).

[0053] Comparative Example 1

[0054] The only difference from Example 1 is that step 2 is omitted, and the remaining steps and parameters are the same as those of Example 1. The prepared catalyst is marked as CZA.

[0055] Example 2

[0056] Two-stage catalyst: composed of the CZA-Ce-0.1NaBH4 catalyst prepared in Example 1 and the commercially available industrial methanol Cu / ZnO / Al2O3 catalyst in the prior art in a volume ratio of 1:1, named CZA-Ce-0.1NaBH4 / industrial catalyst.

[0057] The steps of applying the two-stage catalyst to CO2 hydrogenation to methanol are as follows: the CZA-Ce-0.1NaBH4 catalyst prepared in Example 1 and the commercially available industrial methanol Cu / ZnO / Al2O3 catalyst in the prior art are loaded into the reaction tube by the upper and lower two-stage method, the stack volume ratio of the two catalysts is 1:1, and the total stack volume is 1.5mL. Among them, 0.75mL (about 0.351g) of the CZA-Ce-0.1NaBH4 catalyst is located near the air inlet end (upper), and 0.75mL (about 0.452g) of the commercially available industrial methanol Cu / ZnO / Al2O3 catalyst is close to the air outlet end (lower).

[0058] Comparative Example 2

[0059] The commercially available industrial methanol Cu / ZnO / Al2O3 catalyst in Example 2 is used as a catalyst for producing methanol by hydrogenation of CO2 and is named industrial catalyst.

[0060] Effect verification example 1: The catalysts prepared in Example 1-2 and Comparative Example 1-2 are applied to CO2 hydrogenation to produce methanol

[0061] The catalytic performance evaluation of CO2 hydrogenation was carried out in a fixed bed reactor with an inner diameter of 12 mm. The catalyst (40–60 mesh, 1.5 mL) was loaded in the middle of the reaction tube.

[0062] Before the reaction, the catalyst was reduced at 623K and atmospheric pressure for 6 hours, with a gas flow rate of 80mL / min and V(H2):V(N2)=1:4. After cooling to room temperature, the raw gas with a volume ratio of H2 / CO2=3 / 1 was introduced into the reactor at 3.0MPa or 4.0MPa and 523K, with a total flow rate of 120mL·min -1 Among them, the two-stage catalyst does not involve pre-reduction, and the reaction gas is directly introduced, and the pressure is held to 3.0 or 4.0MPa, and the temperature is raised to 523K.

[0063] The tail gas was analyzed by an online gas chromatograph GC-950N (Nanjing Ganuo Chromatography Technology Co., Ltd.), which was equipped with a thermal conductivity detector (TCD) for detecting CO, CH4 and CO2, and a hydrogen flame detector (FID) for detecting C1-C5 hydrocarbons and alcohols. Data were collected when the reaction remained stable.

[0064] The conversion rate of carbon dioxide (X CO2 ) and product selectivity (S i ) is calculated according to the following formula:

[0065]

[0066] where n i Represents the molar number of carbon atoms in the product, n(CO2) in represents the number of moles of CO2 at the inlet, and g and l represent the gas and liquid products, respectively.

[0067] Discussion on Activity Evaluation Results

[0068] like Figure 1 As shown, compared with the CuZnAl catalyst (CZA) without Ce addition, the CZA catalyst modified by Ce addition has higher CO2 conversion rate and methanol selectivity. It is worth noting that the catalytic performance of each catalyst at 4MPa is significantly improved compared with that at 3MPa. Whether at 3MPa or 4MPa, CZA-Ce-0.1NaBH4 shows the best methanol selectivity. Among them, the CO2 conversion rate (Xco2) of CZA-Ce-0.1NaBH4 at 4MPa is 20.33%, and the methanol selectivity (S CH3OH) is 51.70%. With the continuous increase of NaBH4 dosage, under 4MPa conditions, the methanol selectivity first increased to 51.70% of CZA-Ce-0.1NaBH4, and then decreased to 40.18% of CZA-Ce-0.18NaBH4, and the CO2 conversion rate also showed a similar trend. The catalytic performance of the catalyst under 3MPa follows the same rule as that under 4MPa, indicating that moderate reduction treatment has a positive effect on the catalytic performance of the catalyst. In addition, after the pressure increases, the effect of NaBH4 dosage on methanol selectivity is significantly higher than that on CO2 conversion rate (such as Figure 1 As shown in (d) and (e) above. Figure 1 As shown in (b)-(e), each catalyst exhibited relatively stable catalytic activity under two pressures, and no obvious deactivation occurred during the studied reaction time. The addition of Ce not only improved the catalytic performance, but also significantly improved the stability of the catalyst. Among them, CZA-Ce-0.1NaBH4 and CZA-Ce-0.02NaBH4 were more stable, indicating that the introduction of an appropriate amount of NaBH4 is beneficial to improving the activity and stability of the catalyst.

[0069] Through NaBH4 reduction, Cu and Ce species with different valence states were introduced into the system in order to construct Cu 2+ / Cu δ+ / Cu 0 and Ce 4+ / Ce 3+ The redox electron pairs are used to promote the performance of CO2 hydrogenation to methanol. The effects of NaBH4 dosage on catalyst composition, structure, microscopic species composition, acidity and alkalinity are investigated. The key factors affecting methanol selectivity and CO2 conversion rate are explored, and the reaction mechanism is verified by in situ infrared. Finally, the following conclusions are drawn:

[0070] (1) By adjusting the dosage of NaBH4, the catalytic performance of CO2 hydrogenation to methanol on the catalyst was further improved, showing a trend of first increasing and then decreasing. The CZA-Ce-0.1NaBH4 catalyst (4MPa) showed the best catalytic performance, with a CO2 conversion rate of 20.33% and a methanol selectivity of 51.70%.

[0071] (2) The key factors affecting CO2 conversion include strong alkaline sites and Ce in the catalyst. 3+ Content, Ce 3+ / Ce 4+ ratio, oxygen vacancy content. Among them, Ce 3+ There is a good linear relationship between the content and CO2 conversion rate, which is the most significant influencing factor. The key factors affecting methanol selectivity include the weak acid content in the catalyst, Cu δ+Content and Cu δ+ / (Cu 0 +Cu δ+ ), linear fitting found that Cu δ+ / (Cu 0 +Cu δ+ ) than Cu δ+ The effect of NaBH4 content is more significant, which further indicates that the interaction between species is the key factor affecting methanol selectivity. In summary, the improvement of the comprehensive performance of this series of catalysts may be due to the Ce structure constructed by NaBH4 reduction. 4+ / Ce 3+ , Cu δ+ / Cu 0 Electronic conduction and metal interaction systems.

[0072] (3) In situ infrared characterization results show that, unlike the commonly used Ce-doped catalysts, the main reaction pathways of this series of catalysts are the HCOO* pathway and the RWGS+CO pathway occurring simultaneously.

[0073] like Figure 2 As shown, compared with the single CZA-Ce-0.1NaBH4 catalyst, the catalytic performance after the series reaction has changed significantly, and the methanol selectivity has been greatly improved. On the series-connected catalyst CZA-Ce-0.1NaBH4 / industrial catalyst, the CO2 conversion rate is 9.28%, but the methanol selectivity reaches 85.5%. Comparing the activity data of the single catalyst CZA-Ce-0.1NaBH4 and the industrial methanol catalyst, it is found that the catalyst series reaction combines the advantages of the two catalysts. The CO2 conversion rate is in the middle of the two catalysts, but the selectivity is higher than the two catalysts, and CO is greatly suppressed.

[0074] Depend on Figure 2 The stability data of the catalysts shown in (b)-(d) show that each catalyst exhibits excellent stability during the evaluation period, and the stability of the CZA-Ce-0.1NaBH4 / industrial catalyst is even better ( Figure 2 In (b), there was no obvious deactivation within 504 h of reaction, X CO2 =9.28%, S CH3OH =85.5%.

[0075] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a catalyst, characterized in that: The following steps are involved: The copper-zinc-aluminum catalyst is added into the cerium nitrate aqueous solution and mixed evenly, and then stirred in a water bath to obtain a mixed solution; Adding an alkaline solution of NaBH4 into the mixed solution to react and obtain a precipitate; The precipitate is subjected to ultrasonic treatment, washed, dried, ground and calcined to obtain the catalyst.

2. The method for preparing a catalyst according to claim 1, characterized in that: The concentration of the cerium nitrate aqueous solution is 0.01-0.1 mol / L; the concentration of the copper-zinc-aluminum catalyst in the mixed solution is 60-150 mg / mL; the temperature of the water bath stirring is 303-363 K, and the time is 0.5-4 h.

3. The method for preparing the catalyst according to claim 1, characterized in that: The concentration of NaBH4 in the alkaline solution of NaBH4 is 0-0.20 mol / L; the alkaline solution of NaBH4 also includes NaOH or KOH; the molar ratio of the NaBH4 to the NaOH or KOH is (1-3):

1.

4. The method for preparing the catalyst according to claim 1, characterized in that: The volume ratio of the NaBH4 alkaline solution to the mixed solution is (1-3):1; the reaction is specifically carried out at room temperature for 1-5 hours.

5. The method for preparing the catalyst according to claim 1, characterized in that: The ultrasonic treatment time is 0.5 to 2 hours; the drying temperature is 323 to 353 K, and the time is 8 to 15 hours; the calcination temperature is 583 to 633 K, and the time is 3 to 6 hours.

6. The method for preparing a catalyst according to claim 1, characterized in that: The preparation method of the copper-zinc-aluminum catalyst comprises the following steps: Dissolve copper salt, zinc salt and aluminum salt in water according to the molar ratio of Cu:Zn:Al=2:1:1.2 to obtain solution A; Dissolve the hydroxide and carbonate in water to obtain solution B; The solution A and the solution B are simultaneously dropped into water, stirred, and aged, and the obtained solid is dried and calcined to obtain the copper-zinc-aluminum catalyst; The hydroxide is NaOH or KOH; the carbonate is Na2CO3 or K2CO3.

7. The method for preparing a catalyst according to claim 6, characterized in that: The copper salt is at least one of copper nitrate, copper sulfate, copper acetate or copper chloride; the zinc salt is at least one of zinc nitrate, zinc chloride, zinc sulfate or zinc acetate; the aluminum salt is at least one of aluminum nitrate, aluminum sulfate, aluminum chloride or aluminum acetate; the concentration of the zinc salt in the solution A is 0.2-1.2 mol / L; the concentration of the hydroxide in the solution B is 1-2 mol / L; the molar ratio of the hydroxide to the carbonate is 2:1; the volume ratio of the solution A to the solution B is 1:(1-4); the aging temperature is 353K, and the time is 10-15h; the drying temperature is 343-363K, and the time is 10-15h; the roasting temperature is 583-633K, and the time is 3-6h.

8. The catalyst prepared according to the preparation method according to any one of claims 1 to 7.

9. Use of the catalyst as claimed in claim 8 in producing methanol by hydrogenation of CO2.

10. A two-stage catalyst for producing methanol from CO2 hydrogenation, characterized in that: The catalyst is prepared from the catalyst described in claim 8 and a commercially available industrial methanol Cu / ZnO / Al2O3 catalyst.

Citation Information

Patent Citations

  • Copper-zinc-cerium-based catalyst for low-temperature deep removal of carbon monoxide and preparation method and application of catalyst

    CN104475114A

  • Preparation method of copper based hydrogenation catalyst

    CN104549299A

  • Preparation method of composite material catalyst and application of composite material catalyst at low temperature

    CN109772346A

  • Copper-based catalyst for preparing methanol through carbon dioxide hydrogenation, preparation and applications thereof

    CN111215084A

  • Catalyst for synthesizing methanol by carbon dioxide hydrogenation and preparation method thereof

    CN111790392A

Cited By

  • Oxide catalyst with structure of embedding cerium into zinc-iron spinel as well as preparation method and application of oxide catalyst

    CN119680559A

  • A cerium-embedded zinc-iron spinel structure oxide catalyst, a preparation method and application thereof

    CN119680559B